Manipulating the dimensional assembly pattern and crystalline structures of iron oxide nanostructures with a functional polyolefin. Issue 4 (12th January 2016) - He, Qingliang; Yuan, Tingting; Wang, Yiran; Guleria, Abhishant; Wei, Suying; Zhang, Guoqi; Sun, Luyi; Liu, Jingjing; Yu, Jingfang; Young, David P.; Lin, Hongfei; Khasanov, Airat; et al.
Abstract : Wet chemistry formed Fe2 O3 nanostructures with controlled crystalline structures, morphology, and magnetic properties were achieved by a polyolefin with different concentrations. Abstract : Controlled crystalline structures (α- and γ-phase) and assembly patterns (1-D, 2-D and 3-D) were achieved in the synthesized iron oxide (Fe2 O3 ) nanoparticles (NPs) using polymeric surfactant-polypropylene grafted maleic anhydride (PP- g -MA) with different concentrations. In addition, the change of the crystalline structure from the α- and γ-phase also led to the significantly increased saturation magnetization and coercivity.